FAKTOR-FAKTOR YANG MEMPENGARUHI PRESTASI BELAJAR IPS SISWA KELAS VIII SMPN SATU ATAP PAGA KECAMATAN TANAWAWO (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
This study aims to determine the factors that influence learning achievement in social studies subjects of the eighth grade students of this research conducted at SMPN Satu Atap Paga 2020-2021 semester 1. The method used in this research is descriptive qualitative method. Data obtained through semi-struktured observation and interviews with the parties involved to obtain data on factors that influence student learning achievement in school learning and documentation studies. Data analysis procedures in this study use interactive procedure from Miles and Hubberman which include data collection processes, data reduction, data presentation, and conclusions. The results of the study show that the factors that influence the learning achievement of class VIII students are internal factors that include aspects themselves and external factors which consist of infrastructure.